The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/molecules28237752
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiments for Optimizing Ultrasound-Assisted Extraction of Bioactive Compounds from Plant-Based Sources

Luis Miguel Anaya-Esparza,
Edward F. Aurora-Vigo,
Zuamí Villagrán
et al.

Abstract: Plant-based materials are an important source of bioactive compounds (BC) with interesting industrial applications. Therefore, adequate experimental strategies for maximizing their recovery yield are required. Among all procedures for extracting BC (maceration, Soxhlet, hydro-distillation, pulsed-electric field, enzyme, microwave, high hydrostatic pressure, and supercritical fluids), the ultrasound-assisted extraction (UAE) highlighted as an advanced, cost-efficient, eco-friendly, and sustainable alternative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 150 publications
(293 reference statements)
0
1
0
Order By: Relevance
“…Seven factors were studied: ethanol concentration, liquid:solid ratio (mL/g), kind of sonotrode, amplitude (%), extraction time, extractant pH, and extraction cycle. The studied factors were selected based on preliminary works in our laboratory (data not shown) and consulting bibliography ( Ciğeroğlu et al, 2018 ; Chen et al, 2020 ; Anaya-Esparza et al, 2023 ). The studied runs are given in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven factors were studied: ethanol concentration, liquid:solid ratio (mL/g), kind of sonotrode, amplitude (%), extraction time, extractant pH, and extraction cycle. The studied factors were selected based on preliminary works in our laboratory (data not shown) and consulting bibliography ( Ciğeroğlu et al, 2018 ; Chen et al, 2020 ; Anaya-Esparza et al, 2023 ). The studied runs are given in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…However, optimizing UAE conditions is necessary to minimize the extraction time, solvent consumption, and costs while maximizing efficiency to achieve extracts rich in bioactive compounds with high purity. Moreover, the designs of experiments, such as factorial designs and Plackett–Burman, for screening multiple factors efficiently, or Box–Behnken design, for exploring the intricate relationships between variables, are considered good strategies for carrying out optimization processes ( Anaya-Esparza et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…This increased efficiency is combined with decreased solvent use, which aligns with sustainable standards and contributes to an environmentally benign extraction process [31]. Furthermore, the simplicity of ultrasound-assisted extraction equipment reduces maintenance costs compared to previous methods, highlighting its cost-effectiveness [39]. Beyond extraction efficiency, research has shown that it can increase proteins' physical, structural, and functional characteristics, including solubility, stability, and biological activity.…”
Section: Ultrasound-assisted Protein Extractionmentioning
confidence: 99%
“…In this sense, broccoli leaves have also been shown to be source of GLS, as identified by Ares et al [22], although at a lower concentration than other broccoli tissues [23]. Also, other technologies such as pulsed electric fields have been useful in optimizing the extraction of bioactive compounds [24]. Furthermore, a short microwave-assisted extraction pretreatment, which increased the temperature, favored SFN extraction due to the inactivation of the myrosinase enzymes and GLS-SFN conversion.…”
Section: Introductionmentioning
confidence: 99%